Вы находитесь на странице: 1из 26

# 2001-AL

P MATH
PAPER 2

## HONG KONG EXAMINATIONS AUTHORITY

HONG KONG ADVANCED LEVEL EXAMINATION 2001

## PURE MATHEMATICS A-LEVEL PAPER 2

1.30 pm 4.30 pm (3 hours)
This paper must be answered in English

1.

2.

## Answer ALL questions in Section A and any FOUR questions in Section B.

3.

You are provided with one AL(E) answer book and four AL(D) answer books.
Section B : Use a separate AL(D) answer book for each question and put the
question number on the front cover of each answer book.

4.

The four AL(D) answer books should be tied together with the green tag provided.
The AL(E) answer book and the four AL(D) answer books must be handed in
separately at the end of the examination.

5.

## Unless otherwise specified, all working must be clearly shown.

Hong Kong Examinations Authority
2001-AL-P MATH 21

## FORMULAS FOR REFERENCE

sin( A B) = sin A cos B cos A sin B
cos( A B ) = cos A cos B ! sin A sin B
tan( A B) =

tan A tan B
1 ! tan A tan B

A+ B
A B
cos
2
2
A+ B
A B
sin A sin B = 2 cos
sin
2
2
A+ B
A B
cos A + cos B = 2 cos
cos
2
2
A+ B
A B
cos A cos B = 2 sin
sin
2
2
sin A + sin B = 2 sin

## 2 sin A cos B = sin( A + B) + sin( A B)

2 cos A cos B = cos( A + B ) + cos( A B)
2 sin A sin B = cos( A B) cos( A + B)

2001-AL-P MATH 22

## SECTION A (40 marks)

Answer ALL questions in this section.

1.

(e

e x
.
1 cos 2 x
x

(a)

Find lim

(b)

## Prove that lim x 2 cos

x 0

x 0

1
=0 .
x
(6 marks)

2.

3.

Evaluate
x3

(a)

1+ x

(b)

dx ,

tan 1 x dx .
(5 marks)

Let a1 = 1 and a n +1 =

4 + an
2

## for n N . Show that 1 a n < 2 for all

nN.
Hence show that {a n } is convergent and find its limit.
(6 marks)

4.

) (

(a)

(b)

## If A and B move in such a way that chord AB always passes through

(a, 0) , find the equation of the locus of the mid-point of AB .
(5 marks)

2001-AL-P MATH 23

5.

## Let f be a real-valued function continuous on [0, 1] and differentiable in

(0, 1) . Suppose f satisfies
A.

f(0) = 0 ,

B.

f(1) =

C.

1
,
2
0 < f (t ) < 1 for t (0, 1) .

Define F( x) = 2

x
0

for x [0, 1] .

(a)

(b)

Show that

1
0

## f(t )dt >

1
.
8
(6 marks)

6.

7.

3
x 12 x when
Let f : R R be defined by f(x) =
x
x
+
when
2
ex
e

x2,
x <2.

(a)

(b)

x2

x 2

3
x = cos t ,
:
0 t 2 .
y = sin 3 t ,
(a)

(b)

## Find the area enclosed

by .
(7 marks)

Figure 1
2001-AL-P MATH 24

(5 marks)

## SECTION B (60 marks)

Answer any FOUR questions in this section. Each question carries 15 marks.
Use a separate AL(D) answer book for each question.
2

8.

Let f ( x) = x 3 (6 x) 3 .
(a)

(i)

(ii)

(iii)

8
4
x3

(6

5
x) 3

for x 0, 6 .
(4 marks)

(b)

(i)

f ' ( x) > 0 ,

(ii)

f ' ( x) < 0 ,

(iii)

f '' ( x) > 0 ,

(iv)

f '' ( x) < 0 .
(3 marks)

(c)

(3 marks)

(d)

(2 marks)

(e)

## Sketch the graph of f(x) .

(3 marks)

2001-AL-P MATH 25

y
9.

## In Figure 2, C is the circle

x 2 + ( y + 1) 2 = 4 2 and F is the
point (0, 1) . For any point P on
C , let L p be the perpendicular
bisector of the line segment FP . It
appears that as P moves on C , all
the L p s are tangents to an ellipse
inside C .

LP
P

F
4

2
4
6

Figure 2
(a)

## Suppose for every P on C , the line L p is tangent to the same ellipse.

Write down the equations of the two horizontal tangents and the two
vertical tangents to the ellipse.
Hence guess the equation of the ellipse.
(Note that C is symmetric about the y-axis and F lies on this line of
symmetry.)
(5 marks)

(b)

## Let E be the ellipse found in (a).

(i)

(ii)

2001-AL-P MATH 26

3p
4(q 1)
m=
and n =
. Show that
7q
7q
(I)

M lies on E ,

(II)

FP .

## For any point M on E , show that there is a point P on C such

that the perpendicular bisector of FP is the tangent to E at M .
(10 marks)

10.

(a)

x0

integer n .

(3 marks)
(b)

(ln x)

Show that

(ii)

(i.e. lim+
h 0

1
h

## dx = x(ln x) n n (ln x) n 1dx .

(i)

1
0

ln x dx is convergent

1
0

(ln x) n dx is

(8 marks)
(c)

## Let n be a positive integer and be a positive real number. For

1
1
1
x 1 (ln x) n dx = n +1 (ln x) n dx .
0 < h < 1 , show that
h
h

## Hence show that the improper integral

1
0

x 1 (ln x) n dx is convergent

## and find its value.

(4 marks)

2001-AL-P MATH 27

11.

(a)

## Let f and g be real-valued functions continuous on [a, b] and

differentiable in (a, b) .
(i)

## By considering the function

h( x) = f( x)[g(b) g( a )] g( x)[f(b) f(a )] on [a, b] , or
otherwise, show that there is c (a, b) such that
f (c)[g(b) g(a )] = g (c)[f(b) f( a )] .

(ii)

## Suppose g ( x) > 0 for all x (a, b) . Show that

g( x) g( a ) > 0 for any x (a, b) .
f ( x )
is increasing on (a, b) , show that
g ( x )
f( x) f(a )
P( x) =
is also increasing on (a, b) .
g( x) g( a )
(9 marks)

(b)

Let

e x cos x 1
sin x + cos x 1
Q( x) =
1

if

x 0, ,
4

if

x=0 .

## Show that Q is continuous at x = 0 and increasing on 0, .

4
Hence or otherwise, deduce that for x 0, ,
4

2001-AL-P MATH 28

x
0

Q(t ) dt x .
(6 marks)

12.

(a)

Evaluate
(i)

(ii)

1
2

(x

x +1

dx ,

x 2 +1
2

x + 1)( x 2 + x + 1)

dx .
(6 marks)

(b)

## For n = 1, 2, 3, and 0 x < 1 , define g n ( x) =

h n ( x) =

x 6 r 5
and
r =1 6r 5
n

x 6 r 1
. For any fixed x [0, 1) ,
r =1 6r 1
n

(i)

(ii)

n

(3 marks)
(c)

f n ( x) =
(i)

## For any fixed x (0, 1) , evaluate f n ( x) and show that

lim f ( x) exists.
n

(ii)

x 6 r 5 x 6 r 1
and let f( x) = lim f n ( x ) .

r =1 6r 5
n
6r 1

n

x (0, 1) .

1+ x 2
1+ x 2 + x 4

for

## Hence find f(x) .

(6 marks)

2001-AL-P MATH 29

13.

f(1 + x) =

(a)

f( x )
for all x .
1 + f( x)

## Show that for any n N and x R , f(n + x) =

f( x)
.
1 + n f( x)
(3 marks)

(b)

Define x n = 1 +

f(1)
n +1
for any n N . Show that f( x n ) =
.
1 + n f(1)
n+2

n

1
1
and f = n .
n
n
(5 marks)

(c)

## For any q N and q 2 , let S(q) be the statement

p q
f =
for all p N with 0 < p < q .
q p
(i)

(ii)

## Assume that S(h) is true for 2 h q and h N . Use (a) to

q +1
p
=
for 0 < p < q + 1.
show that f
p
q
+1

(iii)

1
f( x) = .
x
(7 marks)
END OF PAPER

## 2001-AL-P MATH 210

2001 Paper 2
Section A
1.

(a)

2.

(a)

x2 1
ln(1 + x 2 ) + c
2 2

(b)

x3
x2 1
tan 1 x
+ ln(1 + x 2 ) + c
3
6 6

3.

4.

(a)

2 x (t1 + t 2 ) y + 2at1t 2 = 0

(b)

y 2 = 2ax 2a 2

6.

(b) No

7.

(a)

(b)

2001 Paper 2
Section B

8.

(a)

(i)

f (x) =

1 3
x (6 x) 3 [2(6 x) x]
3

= x

(ii) Since

2 3
1
x ( 6 x ) 3 x 3 (6 x ) 3
3
3

1
3

(6 x )

2
3

for x 0, 6

(4 x)

f (0) = lim
h 0

2
h3

1
(6 h) 3

6 3
= lim 1 = ,
h 0 h

6 3
f + (0) = lim+ 1 = ,
h 0 h

(6 + h) 3 ( h) 3
6 3
= lim + 1 = , and
f (6) = lim
h 0
h 0
h
h
2

6 3
f + (6) = lim+ + 1 = ,
h 0
h
therefore both f ' (0) and f ' (6) do not exist.
4

1
2
(iii) f (x) = x 3 (6 x) 3 (4 x) + x 3 (6 x) 3 (4 x) x 3 (6 x) 3
3
3
4

1
= x 3 (6 x) 3 [ (6 x)(4 x) + 2 x (4 x) 3 x(6 x )]
3
8
= 4
for x 0, 6
5

x 3 (6 x ) 3

2001 Paper 2
Section B
f (x) > 0

(b) (i)

(c)

0<x<4

x>6

(, 0)

(0,4)

(4,6)

(6,)

Undefined
Undefined

f(x)

5
23

f (x)
f (x)

Undefined
Undefined

## One relative minimum point:

One relative maximum point:
One point of inflexion:

(0, 0) .
5
23

(4, ) .
(6, 0) .
1

(d) Since

f( x)
6 3
lim
= lim 1 = 1 , and
x x
x x

lim [f( x) + x ]

6 3
1 + 1
1
2

x
= lim x 3 (6 x) 3 + x = lim
x
1
x

therefore

6 3
= lim 2 1
=2,
x x

2001 Paper 2
Section B
(e)

y

(4, 2 3 )

(6,0)

y = x + 2

2001 Paper 2
Section B
9.

(a)

## P1 = (0, 3) and P2 = (0, 5) are the two points on C such that

P1 F and P2 F are vertical.

i.e.

y = 2 .

## P3 = 2 3 , 1 and P4 = 2 3 , 1 are the two points on C such that

P3 F and P4 F are horizontal.

## The two vertical tangents to the ellipse are L P3 and L P4 .

i.e.

x= 3 .

Since the circle is symmetric about the y-axis and F also lies on
this line of symmetry, the ellipse must also be symmetric about the y-axis.
Thus one of the axes of symmetry of the ellipse is vertical.
Since y = 2 are the horizontal tangents,
the end-points of this vertical axis of the ellipse must be (0, 2) .
This implies that the centre of the ellipse is the origin and the other axes of
symmetry is horizontal and passes through the origin.
Since x = 3 are the vertical tangents,

2

## The equation of the ellipse is

x y

+ =1

3 2

4 x 2 + 3 y 2 = 12

2001 Paper 2
Section B
(b) (i)

(I)

Since P lies on C ,

p 2 + q 2 + 2q 15 = 0 .

## Putting M into the equation of E , we have

LHS =
=

(7 q ) 2
12
(7 q ) 2
12

48(q 1) 2
(7 q ) 2

[3(q

2q + 15) + 4(q 2 2q + 1)

q 2 14q + 49
(7 q ) 2
= 12 = RHS
M lies on E .
=

36 p 2

## (II) The equation of the tangent, TM , at M to E is

4mx + 3ny = 12
or
px + (q 1) y + (q 7) = 0 .
Slope of TM = mTM =
Slope of FP = m FP =

12 p
p
4m
=
=
.
12(q 1)
q 1
3n

q 1
.
p

mTM m FP = 1 .

p q +1
Putting the mid-point of FP , ,
, into the equation of TM :
2
2
p 2 (q 1)(q + 1)
+
+ ( q 7)
2
2
1
= (q 2 2q + 15) + (q 2 1) + 2(q 7)
2
= 0 = RHS .

LHS =

2001 Paper 2
Section B

## (ii) Let M(m, n) be any point on E . Solving m =

we have p =

3p
4(q 1)
and n =
,
7q
7q

8m
7n + 4
and q =
.
n+4
n+4

Since M lies on E , 4m 2 + 3n 2 = 12 .
Let P be the point (p, q) and put (p, q) into C ,
LHS =
=

64m 2
(n + 4) 2

64(n + 1) 2
( n + 4) 2

16(3n 2 + 12 + 4n 2 + 8n + 4)

( n + 4) 2
= 16 = RHS .
P lies on C .
4(n + 1)
4m
,
Mid-point of FP =
.
n
4
n+4
+

3n
.
4m
Equation of the perpendicular bisector of FP is
(n + 4) y 4(n + 1)
4m
=
( n + 4) x 4m
3n
Slope of FP =

## 3n(n + 4) y 12n(n + 1) = 4m(n + 4) x + 16m 2

4m(n + 4) x + 3n(n + 4) y = 12n(n + 1) + 4(12 3n 2 )
4m(n + 4) x + 3n(n + 4) y = 12(n 2 + n + 4 n 2 )
4mx + 3ny = 12
which is the same as the equation of the tangent to E at M .

2001 Paper 2
Section B

10. (a)

lim x(ln x) 0 = 0 .

For n = 0 ,

x0+

x0

x0

(ln x) k +1
x 1

x 0

= lim+

(k + 1)(ln x) k

## [by LHospital rule]

x 1

x0

= 0
[by induction hypothesis]
By the principle of mathematical induction, the result follows.
(b) (i)

## Using the method of integration by parts,

d
(ln x) n dx = x(ln x) n x ( ln x) n dx
dx

## (ii) For 0 < h < 1 ,

1
h

ln x dx = [x ln x x ]1h = 1 h ln h + h

h 0

1
0

h 0

ln x dx = lim+
h 0

## for any positive integers n .

1
h

1
h

ln x dx exists and

ln x dx = 1

## For 0 < h < 1 and any positive integer n ,

1
h

(ln x) n dx = x(ln x) n

] n (ln x)
1

1
h

n 1

dx

= h(ln h) n n x(ln x) n 1 h (n 1)

## = h(ln h) n + nh(ln h) n1 + n(n 1)

(ln x)

n 2

(ln x)
h

n2

dx

dx


= h(ln h) n + nh(ln h) n 1  + (1) n (n! )h(ln h) + (1) n (n! )
Since lim+ h(ln h) k = 0 (k = 0, 1, 2, ) by (a),
h 0

lim+

h 0
1

1
h

(ln x)
0

dx

= lim+
h 0

1
h

## (ln x) n dx = (1) n (n!)

1
h

dx

2001 Paper 2
Section B

(c)

Let y = x , > 0 .
Then

dy
= x 1 and
dx

1
h

x 1 (ln x ) n dx =
=

Since lim+
h 0

lim+

h 0

1
0

1
h

1
h

1
h

1
1
( ln y ) n dy

n +1

1
h

(ln x) n dx

## x 1 (ln x ) n dx exists and

x 1 (ln x) n dx = lim+
h 0

n +1

(1) n n!

n +1

(ln x) n dx =

2001 Paper 2
Section B
11. (a)

(i)

## h( a ) = f(a )[g(b) g(a )] g( a )[f(b) f(a )] = f(a ) g(b) f(b) g( a ) and

h(b) = f(b)[g(b) g(a )] g(b)[f(b) f(a )] = f(a ) g(b) f(b) g(a )
h(a) = h(b)
Since h is continuous on [a, b] and differentiable in (a, b) ,
there is a c (a, b) such that
h (c) = 0
[Mean Value Theorem]
i.e. f (c)[g(b) g(a )] = g (c)[f(b) f(a)]
g ( x) > 0 for all x (a, b) ,

(ii) Since

## g(x) is strictly increasing on (a, b)

By the continuity of g at x = a , g(x) > g(a) for any x (a, b) .
i.e. g( x) g( a ) > 0 for any x (a, b) .
For any x (a, b) ,
[g( x) g( a)] f ( x) [f( x ) f(a )] g ( x)
.
P ( x) =
[g( x) g( a )] 2
Using the result of (a) and for x (a, b) ,
f (c )
f( x) f(a )
P(x) =
=
for some c (a, x)
g( x) g( a )
g (c )
f ( x )
f (c )
f ( x )
Since
is increasing,

.
g ( x )
g (c )
g ( x )
f ( x )
f( x) f(a )

Hence
g( x) g( a )
g ( x )

i.e.

[g( x) g( a )] f ( x) [f( x) f( a )] g ( x) 0
P ( x) 0

## P(x) is also increasing on (a, b) .

2001 Paper 2
Section B
(b) Using LHospital rule,
e x (cos x sin x)
e x cos x 1
= lim+
= 1 = Q(0)
x 0 sin x + cos x 1
x 0
cos x sin x
Q is continuous at x = 0 .

lim+ Q( x) = lim+

x 0

Now, Q is continuous on 0, and differentiable in 0, .
4
4

Putting f(x) = e x cos x and g(x) = sin x + cos x , then for x 0, ,
4
g ( x) = cos x sin x > 0 and
f ( x) e x (cos x sin x)

=
= e x which is increasing on 0, .
g ( x)
cos x sin x
4
f( x) f(0)
e x cos x 1

Now for x 0, , Q(x) =
=
.
4
g(
x) g(0)
sin
+
cos

1
x
x

Using the result in (a)(ii) and the fact that Q is continuous on 0, ,
4

Q is increasing on 0, .
4

Hence Q(x) Q(0) = 1 for x 0, ,
4

x
0

Q(t ) dt

x
0

dt = x for x 0, .
4

2001 Paper 2
Section B

12. (a)

1
2

x +1

(x

dx =

1
1 2
)
2

+(

3 2
)
2

dx

x 1

2
tan 1
+c
3
3
2
2
2x 1
2
+c
tan 1
=

3
3
1

Let

x 2 +1
2

( x x + 1)( x + x + 1)

ax + b
2

x x +1

cx + d

for some a, b, c, d R .

x + x +1

## x 2 + 1 (ax + b)( x 2 + x + 1) + (cx + d )( x 2 x + 1)

Then

a = c = 0, b = d =

(x

Hence
=

1
2

1
.
2

x 2 +1
2

dx

x + 1)( x 2 + x + 1)

dx +

1
2

dx
x +1
+ x +1
2x 1 1
2x +1
1
+
+c
tan 1
tan 1
=

3
3
3
3
2

## (b) For n = 1, 2, 3,  and any fixed x [0, 1) ,

x 6( n +1) 5
x 6( n +1) 1
(i) g n +1 ( x) g n ( x) =
0 and h n +1 ( x) h n ( x) =
0 .
6(n + 1) 5
6(n + 1) 1

(ii)

{g n ( x)}

g n ( x) =

x 6 r 5

r =1 6r 5
n

n
r =1

x 6 r 5 =

x(1 x 6 n )
1 x

x
1 x 6

n
x5
x 6 r 1
x 5 (1 x 6 n )
x 6 r 1 =

6
r =1 6r 1
r =1
1 x
1 x 6
Both {g n ( x )} and {h n ( x)} are bounded above.

h n (x ) =

## Using (i), lim g n ( x) and lim h n ( x) exist.

n

2001 Paper 2
Section B

(c)

Let n = 1, 2, 3,  .
(i)

## For any fixed x (0, 1) ,

n
x 6 r 6 x 6 r 2
f ( x) =

(
= (1 + x + x

r =1
6

12

+  + x 6( n 1) x 4 1 + x 6 + x 12 +  + x 6( n 1)

(1 x )(1 x

6n

1 x
Since 0 < x <1 , x 6 n 0 as n .
lim f ( x) exists.

f ( x) = lim f n ( x)

## (ii) For x (0, 1) ,

=
=

Hence

f(x) =
=
=
=

1 x 4
1 x6
1+ x 2
1+ x 2 + x 4

1+ x2

1+ x
(x
(x

+ x4

dx

x 2 +1
2

+ 1) 2 x 2

dx

x 2 +1
2

x + 1)( x 2 + x + 1)

dx

2x 1 1
2x +1
+
+c
tan 1
tan 1

3
3
3
3

for x (0, 1)
Noting that f(0) = 0 since f n (0) = 0 for all n and that f is
continuous on [0, 1) , we have c = 0 .
2x 1 1
2x +1
1
+

i.e. f(x) =
tan 1
tan 1

3
3
3
3

2001 Paper 2
Section B

13. (a)

## Using the given condition, f(1 + x) =

f( x)
.
1 + f( x)

f( x)
where k Z+ . Then
1 + k f( x)
f(k + x)
f[(k + 1) + x] =
1 + f(k + x)
f( x)
1 + k f( x)
=
f( x)
1+
1 + k f( x)
f( x)
.
=
1 + (k + 1) f( x)
By the principle of mathematical induction, the result follows.

Assume f(k + x) =

(b)

f(1)
f( x n ) = f 1 +

1
n f(1)
+

f(1)
f

1 + n f(1)
=
f(1)
1+ f

1 + n f(1)
=

f[f(n + 1)]
1 + f[f(n + 1)]

n +1
n+2
By the continuity of f ,
=

n +1
f(1) = f lim x n = lim f( x n ) = lim
=1
n n + 2
n n
For n > 1 ,
f(n) = f[(n 1) + 1]

For n N ,

f(1)
1 + (n 1) f(1)

1
n

1
f = f[f(n)] = n
n

( by (a) )

2001 Paper 2
Section B

(c)

(i)

1
From (b), f = 2 . S(2) is true.
2

## (ii) Assume that S(h) is true for 2 h q and h N .

For 0 < p < q + 1 , there are , N with 0 < p such that
q + 1 = p + .

q +1

= f +
f
p
p

()
=
1+ f ( )
f

1+

()
p

[from (a)]

## [by induction hypothesis]

p
p
+
p
=
q +1

q + 1
p q +1
p
= f
=
, f
f f
p
q
1
p

+
q +1

i.e. S(q + 1) is true.

Hence

2001 Paper 2
Section B
(iii) From (i), S(2) is true.
From (ii), assuming that S(h) is true for 2 h q ,
it is proved that S(q + 1) is true.
By the principle of mathematical induction, S(q) is true for q = 2, 3, 4, 
For any positive rational number x ,
1
by (b).
x
(II) If x is not an integer, then x = n + r for some
non-negative integer n and 0 < r < 1 .
p
where p, q N and 0 < p < q .
Let r =
q

(I)

If x is an integer, then f( x) =

Then

p
)
q

f(x) = f(n +

()
=
1+ nf ( )
p
q

p
q

q
p

1+ n
1

n+
=

1
x

p
q

q
p

[by (a)]